RELATIONSHIPBETWEEN THE SCHOOLPERFORMANCE AND PSYCHOMOTOR PROFILE (Fiep Bulletin - online, 2013)
Following the daily life of a public school, you may realize that the problems of children are growing and that, every day, the school suffers falls. Deviations in psychomotor factors are also related to learning. Changes in these factors can highlight important relationship with learning difficulties (SANCHES; WAR; LUFT and ANDRADE, 2004). This study aimed to investigate whether there is relationship between school performance and psychomotor profile, its general objective is to compare the profile of psychomotor school students from low income and good school performance of the 1st cycle of training elementary school. This study is characterized as a field research, the type comparison. The research involved a sample of n = 40 (forty), children of the 1st cycle of training elementary school, with n1 = 20 children with low school performance and n2 = 20 children with good school performance of both sexes, forming a group of volunteers, all residents of the West Zone of the City of Rio de Janeiro. The instrument used was part of the protocol for assessing Psychomotor Battery of Vitor da Fonseca (1995). Comparing the level of general psychomotor development among groups of the sample population was a difference in those values, and the group of low-income school [GR: R] showing average (2.84 ± 0.20) and group of good yield school has obtained an average of (3.66 ± 0.19) it is concluded therefore that in the sample group of children from low-income school there were failures in psychomotor performance, especially in Concept of Body and Space-Time Structure functions, being observed more obvious and more significant differences in these functions.
Keywords: Psychomotricity; learning; school income